Gravidez e anticorpos antifosfolípidos em doentes com lúpus eritematoso sistémico: uma avaliação do prognóstico - Cordeiro, Alexandra (2017)
Background and aims: Antiphospholipid antibodies (APLAs) have been associated with pregnancy loss and other obstetric complications, such as pre-eclampsia, fetal growth restriction and preterm delivery. Systemic lupus erythematosus (SLE) patients frequently present APLAs and secondary antiphospholipid syndrome. The purpose of this work is to evaluate pregnancy outcome in SLE patients with and without APLAs. Material and Methods: Retrospective analysis of 136 gestations in women with SLE diagnosis previous to pregnancy that underwent surveillance in our maternity from 1993 to 2007. Patients with and without APLAs were considered separately. Maternal age, obstetric history, SLE activity and nephropathy, present pregnancy evolution, gestational age at delivery, mode of delivery, birth weight and hypertensive complications were identified. Results: 28% (38) of pregnant SLE patients had APLAs. From these patients, 28.9.8% had past history of second and/or third trimester fetal losses, against 6.12% in patients without APLAs (p<0.05). Evaluation of present pregnancy outcome revealed, for APLAs positive patients, a significant higher rate of non-successful pregnancy (8.1% vs; 2.1%, p<0.05). Analysis of mean birth weight and intrauterine growth restriction rates revealed no signifi-cant differences related to APLAs presence. Mean gestational age at delivery was 36.9 weeks for both groups with identical preterm delivery rates. Cesarean section was the mode of delivery for 47% and 44.1% of the patients, in APL patients and others, respectively. Conclusions: SLE patients with APLAs had more spontaneous abortions and worse obstetric history, with no other significant differences in perinatal and obstetric outcome.